1999
DOI: 10.1038/sj.bmt.1701913
|View full text |Cite
|
Sign up to set email alerts
|

Optic disc and retinal microvasculopathy after high-dose chemotherapy and autologous hematopoietic progenitor cell support

Abstract: Summary:The purpose of this study was to prospectively evaluate the retinal and optic nerve changes in patients undergoing high-dose chemotherapy (HDC) followed by autologous hematopoietic progenitor cell support (AHPCS). One hundred and forty patients undergoing HDC and AHPCS underwent extensive pre-and post-transplant ophthalmologic evaluations for development of retinal microvascular complications. One hundred and ten patients received high-dose cyclophosphamide, cisplatin and BCNU; thirty received identica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 10 publications
0
18
2
Order By: Relevance
“…Three of them were first found to have these changes 5 years after BMT, their fundi having been recorded as normal in the intervening period. This again contrasts strongly with previous accounts where the occlusive changes were seen mostly within the first 6 months, 1,3,5–8,11 the latest being at 2 years 2,4,10 …”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Three of them were first found to have these changes 5 years after BMT, their fundi having been recorded as normal in the intervening period. This again contrasts strongly with previous accounts where the occlusive changes were seen mostly within the first 6 months, 1,3,5–8,11 the latest being at 2 years 2,4,10 …”
Section: Discussioncontrasting
confidence: 98%
“…Retinal microvascular changes after bone marrow transplantation (BMT) have been well described 1–11 . Studies to date have focused on identifying the factors in conditioning therapy and graft‐versus ‐ host disease (GVHD) prophylaxis that are most associated with its development.…”
Section: Introductionmentioning
confidence: 99%
“…23 In people, posterior segment toxicity with cotton wool spots, retinal hemorrhage, or optic disc edema has been reported in patients treated with IV, intra-arterial, or combination chemotherapy with 1,3 bis(2-chloroethyl)-1-nitrosourea (BCNU). 24,25 One of the authors has observed similar lesions in a dog treated with BCNU and radiation (C.G. Couto, personal communication).…”
Section: Discussionmentioning
confidence: 76%
“…This was reversed on discontinuing CDDP. Previously reported ophthalmic complications associated with CDDP chemotherapy include macular retinal pigment abnormality, retinal ischaemia with neovascularisation, retinal microvascular complications, subclinical retinal dysfunction, cone dysfunction, optic neuropathy and cortical blindness [5][6][7][8][9][10][11]. To the best of our knowledge this is the first case report of reversible branch retinal artery occlusion from CDDP therapy.…”
Section: Commentmentioning
confidence: 91%